New Insight Into the Structure-Activity Relationship of Sweet-Tasting Proteins: Protein Sector and Its Role for Sweet Properties - Zhao, Xiangzhong; Wang, Congrui; Zheng, Yue; Liu, Bo (Frontiers in Nutrition, 2021)
Sweet-tasting protein is a kind of biomacromolecule that has remarkable sweetening power and is regarded as the promising sugar replacer in the future. Some sweet-tasting proteins has been used in foods and beverages. However, the structure and function relationship of these proteins is still elusive, and guidelines to direct their protein engineering is limited. It is well-known that the sweet-tasting proteins bind to and activate the sweet taste receptor T1R2/T1R3, thus eliciting their sweetness. The “wedge-model” for describing the interaction between sweet-tasting proteins and sweet taste receptor to elucidate their sweetness has been reported. In this perspective article, we revealed that the intramolecular interaction forces in sweet-tasting proteins is directly correlated to their properties (sweetness and stability). This intramolecular interaction pattern, named as “protein sector”, refers to a small subset of residues forming physically connections, which cooperatively affect the function of the proteins. Based on the analysis of previous experimental data, we suggest that “protein sector” of sweet-tasting proteins is pivotal for their sweet properties, which are meaningful guidelines for the future protein engineering.